1997
DOI: 10.1111/j.1440-1746.1997.tb00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Gall‐bladder wall thickening in patients with liver cirrhosis

Abstract: Gall-bladder wall thickening is commonly seen in patients with cirrhosis, but its exact causes have not been well established. We evaluated clinical, biochemical and haemodynamic data of patients with cirrhosis with respect to the presence of thickening of the gall-bladder wall. After excluding patients who presented with gallstones, acute or chronic cholecystitis, heart failure, a serum creatinine level greater than 2 mg/dL and/or a serum alanine aminotransferase level greater than 400 U/L, 77 patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
22
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
6
22
0
Order By: Relevance
“…9 In this study, presence of ascites, lower level of albumin, and lower platelet count were identified as independently In their study, portal hypertensionVdirectly measured by calculation of hepatic venous pressure gradient (HVPG)Vwas not, however, statistically significant albeit showing a tendency for association. 8 Although the associating factors were somewhat different among these studies, our results were overall concordant with those of previous investigations. The pathophysiologic mechanism for DGWT in the patients with liver cirrhosis has not been clearly understood.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…9 In this study, presence of ascites, lower level of albumin, and lower platelet count were identified as independently In their study, portal hypertensionVdirectly measured by calculation of hepatic venous pressure gradient (HVPG)Vwas not, however, statistically significant albeit showing a tendency for association. 8 Although the associating factors were somewhat different among these studies, our results were overall concordant with those of previous investigations. The pathophysiologic mechanism for DGWT in the patients with liver cirrhosis has not been clearly understood.…”
Section: Discussionsupporting
confidence: 94%
“…11 Therefore, cholecystic venous outflow would be impaired in case of increased hepatic vascular resistance, resulting in venous congestion of the gallbladder manifesting as DGWT on cross-sectional imaging. However, the study by Wang et al,8 in which portal hypertension was measured by HVPG, failed to show a significant association between portal hypertension and DGWT, as mentioned above. In addition, Loreno et al 9 reported that DGWT developed in almost all Child-Pugh class A cirrhotic patients without portal hypertension.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This has led to a drastic increase of GD prevalence in HBsAg positive population. As for gender, our results are consistent with the generally accepted view that gallstone prevalence is higher in women than in men [32,33]. Quite a few studies revealed a positive correlation between a high serum LDL level and cholesterol gallstone development [34,35]; the results of our study displayed a relationship between a high serum LDL level and GD prevalence, though we failed to get the information of the gallstone type.…”
Section: Discussionsupporting
confidence: 82%